After 4 interval of six months, Joe to earn same hourly rate as Blaine
<em><u>Solution:</u></em>
Given that,
Amount earned by Joe = $ 14 per hour
Amount earned by Blaine = $ 18 per hour
Lets assume the number of six month intervals be "x"
<em><u>Joe receives a raise of $1.75 every six months</u></em>
Therefore,
Joe earning: 14 + 1.75(number of six month intervals)
Equation for Joe earning: 14 + 1.75x ------- eqn 1
<em><u>Blaine receives a raise of $0.75 every six months</u></em>
Therefore,
Blaine earning: 18 + 0.75(number of six month intervals)
Equation for Blaine earning: 18 + 0.75x ------------ eqn 2
The number of six-month intervals it will take Joe to earn the same hourly rate as Blaine,
Eqn 1 must be equal to eqn 2
![14+1.75x = 18+0.75x\\\\1.75x-0.75x = 18-14\\\\1x = 4\\\\x = 4](https://tex.z-dn.net/?f=14%2B1.75x%20%3D%2018%2B0.75x%5C%5C%5C%5C1.75x-0.75x%20%3D%2018-14%5C%5C%5C%5C1x%20%3D%204%5C%5C%5C%5Cx%20%3D%204)
Thus after 4 interval of six months, Joe to earn same hourly rate as Blaine.
Answer:
V = −1
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
3=−2v−v
3=−2v+−v
3=(−2v+−v)(Combine Like Terms)
3=−3v
3=−3v
Step 2: Flip the equation.
−3v=3
Step 3: Divide both sides by -3.
<u>−3v</u> = <u>3</u>
-3 -3
v=−1
So you want to find the area of each side
8X10=80
8x6=48
8x8=64
10X6=60
80+48+64+60=252
So the surface area is 252 yds
9514 1404 393
Answer:
B. (2, 0)
Step-by-step explanation:
We understand the points on the graph of h(x) to be ...
(0, 2), (1, 5), (2, 8), (3, 11), (4, 14), (5, 17)
The points on the graph of the inverse function will have the x- and y-coordinates reversed:
(2, 0), (5, 1), (8, 2), (11, 3), (14, 4), (17, 5)
The one that appears among the answer choices is ...
(2, 0)
Answer:
1. x = 2
2. x = 61/25
Step-by-step explanation:
Solve for x:
5 (x - 2) - 3 (2 - x) = 0
-3 (2 - x) = 3 x - 6:
3 x - 6 + 5 (x - 2) = 0
5 (x - 2) = 5 x - 10:
5 x - 10 + 3 x - 6 = 0
Grouping like terms, 5 x + 3 x - 10 - 6 = (3 x + 5 x) + (-6 - 10):
(3 x + 5 x) + (-6 - 10) = 0
3 x + 5 x = 8 x:
8 x + (-6 - 10) = 0
-6 - 10 = -16:
8 x + -16 = 0
Add 16 to both sides:
8 x + (16 - 16) = 16
16 - 16 = 0:
8 x = 16
Divide both sides of 8 x = 16 by 8:
(8 x)/8 = 16/8
8/8 = 1:
x = 16/8
The gcd of 16 and 8 is 8, so 16/8 = (8×2)/(8×1) = 8/8×2 = 2:
Answer: x = 2
_____________________________
Solve for x:
Solve for x:
3 (2 x - 7) + (7 x + 2)/3 = 0
Put each term in 3 (2 x - 7) + (7 x + 2)/3 over the common denominator 3: 3 (2 x - 7) + (7 x + 2)/3 = (9 (2 x - 7))/3 + (7 x + 2)/3:
(9 (2 x - 7))/3 + (7 x + 2)/3 = 0
(9 (2 x - 7))/3 + (7 x + 2)/3 = (9 (2 x - 7) + (7 x + 2))/3:
(9 (2 x - 7) + 2 + 7 x)/3 = 0
9 (2 x - 7) = 18 x - 63:
(18 x - 63 + 7 x + 2)/3 = 0
Grouping like terms, 18 x + 7 x - 63 + 2 = (18 x + 7 x) + (2 - 63):
((18 x + 7 x) + (2 - 63))/3 = 0
18 x + 7 x = 25 x:
(25 x + (2 - 63))/3 = 0
2 - 63 = -61:
(25 x + -61)/3 = 0
Multiply both sides of (25 x - 61)/3 = 0 by 3:
(3 (25 x - 61))/3 = 3×0
(3 (25 x - 61))/3 = 3/3×(25 x - 61) = 25 x - 61:
25 x - 61 = 3×0
0×3 = 0:
25 x - 61 = 0
Add 61 to both sides:
25 x + (61 - 61) = 61
61 - 61 = 0:
25 x = 61
Divide both sides of 25 x = 61 by 25:
(25 x)/25 = 61/25
25/25 = 1:
Answer: x = 61/25